2017
DOI: 10.5301/ijao.5000583
|View full text |Cite
|
Sign up to set email alerts
|

Hemoadsorption Treatment of Patients with Acute Infective Endocarditis during Surgery with Cardiopulmonary Bypass - A Case Series

Abstract: IntroductionInfective endocarditis is a serious disease condition. Depending on the causative microorganism and clinical symptoms, cardiac surgery and valve replacement may be needed, posing additional risks to patients who may simultaneously suffer from septic shock. The combination of surgery bacterial spreadout and artificial cardiopulmonary bypass (CPB) surfaces results in a release of key inflammatory mediators leading to an overshooting systemic hyperinflammatory state frequently associated with compromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
98
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(110 citation statements)
references
References 15 publications
10
98
1
1
Order By: Relevance
“…On the other hand, studies have also suggested that the use of colloids is the best strategy to maintain intravascular volume and haemodynamic stability. Paradoxically, studies also advise fluid restricting patients, as Stewart et al have previously demonstrated a reduction in ICU stay and more ventilator-free days in cardiac surgery patients who underwent conservative fluid management [49] .…”
Section: G Duration Of Cpbmentioning
confidence: 99%
“…On the other hand, studies have also suggested that the use of colloids is the best strategy to maintain intravascular volume and haemodynamic stability. Paradoxically, studies also advise fluid restricting patients, as Stewart et al have previously demonstrated a reduction in ICU stay and more ventilator-free days in cardiac surgery patients who underwent conservative fluid management [49] .…”
Section: G Duration Of Cpbmentioning
confidence: 99%
“…A recently published prospective single-center study by Friesecke and coworkers in twenty patients with septic shock refractory to standard treatment that were treated with CytoSorb showed a significant reduction in norepinephrine dosages and shock reversal in two thirds of the patients [19]. Likewise, patients undergoing cardiopulmonary bypass-assisted cardiac surgery (including those with endocarditis) who developed post-operative hyperinflammation, showed a marked benefit from hemoadsorption treatment in terms of hemodynamic stabilization and reduction in catecholamine dosages [2,20].…”
Section: Discussionmentioning
confidence: 99%
“…3]. Less vasopressor was needed during the operation, and fewer renal replacement therapy implemented after the surgery in patients who used Cytosorb connected to the cardiopulmonary by-pass [23,24]. In a study performed by Gleason et al, patients with haemoadsorption had a significantly lower free haemoglobin and activated complement serum concentrations [25].…”
Section: State Of Knowledgementioning
confidence: 99%